Electrical and mechanical charaterization of silicon and zinc oxide nanowires - Hoffmann, Samuel (My University, 2008)
Semiconducting nanowires can be grown epitaxially on crystalline substrates in predefined directions. This bottom up approach stands in contrast to the common top down technology in semiconductor industry. With diameters down to a few nanometers, the nanowires’ small dimensions open up new possibilities for sensors and electronic devices. This thesis deals with the electrical, mechanical, and electromechanical characterization of silicon and zinc oxide nanowires. Their small dimensions reveal difficulties for the investigation of their properties. Common methods are used when possible, and new techniques are developed where standard methods reach their limits. The doping concentration of nanowires doped during growth is measured by contacting them using electron beam lithography. It is shown that by adding phosphine or diborane to the growth chamber, n and p doping concentrations in the order of 1019 cm−3 can be achieved. A careful analysis reveals that the doping concentration changes along the nanowire axis. p-n junctions along the nanowire axis are achieved by ion implantation after the nanowire growth. Because of the limited penetration depth of the dopant ions, this new doping process applies to rather short nanowires (<500 nm), only, so it is difficult to contact them by electron beam lithography. Alternatively, a novel method allowing the location of junctions at the nanometer scale is introduced. This method is based on a nanomanipulator built into a scanning electron microscope that is used to contact the nanowires, and the p-n doping profile is revealed by electron beam induced current imaging. The presented technique is able to qualitatively demonstrate the effective doping of very short individual nanowires. The nanomanipulator inside the scanning electron microscope used for the electrical investigations was originally developed to manipulate the nanowires for mechanical characterizaition. In contrast to traditional characterization techniques based on atomic force microscopy, a versatile tool is introduced that allows for fast characterization of nanostructures with real time visual feedback from the scanning electron microscope. In particular, tensile experiments can be performed in which the specimen is strained uniformly. This is important to reduce the influence of surface effects, for example when measuring Young’s modulus of a material. In order to precisely and automatically extract data from the experiments, an image analysis tool is programmed that can track objects with subpixel resolution. Further, finite element calculations show within which limits the analytic elastic beam formula can be used to calculate the maximum strain at the nanowire footing, taking into account its particular shape and the nanowires low aspect ratio. Mechanical investigations reveal that the fracture strength of both silicon and zinc oxide nanowires is close to the theoretical limit. Subjected to bending experiments, silicon and zinc oxide nanowires show a fracture strain of (6.3±1.8)% and (7.7±0.8)% (average ± 1 standard deviation), respectively. Because of the controversial values published on Young’s modulus of zinc oxide nanowires, these are subjected to tensile load as well. The tensile strength is 4 GP a, and Young’s modulus is measured to be 100 GPa, close to the bulk value of 144 GPa. Finally, an experiment for the measurement of electromechanical properties of silicon nanowires is proposed. It shows that the nanowires can be strained close to their fracture limit while measuring the electrical properties. We expect that the new measurement techniques developed in this work can be applied to a large number of different nanowires and microstructures, speeding up characterization and thus contributing to an efficient development of new materials and devices.
Thèse de doctorat : Université de Neuchâtel, 2008 ; Th. 2067
Keywords: nanofils silicium; nanofils oxyde de zinc; propriétés électriques; propriétés mécaniques; silicon nanowires; zinc oxide nanowires; electrical properties; mechanical properties